Setting time and thermal expansion of two endodontic cements - Santos, Alailson D. [UNESP]; Araujo, Eudes B. [UNESP]; Yukimitu, Keizo [UNESP]; Barbosa, Jose C. [UNESP]; Moraes, João Carlos Silos [UNESP] (Mosby-elsevier, 2008)
The purpose of this study was to evaluate the setting time and the thermal expansion coefficient of 2 endodontic cements, MTA-Angelus and a novel cement called CER. The setting time was determined in accordance to ANSI/ADA specifications no. 57. Three samples of 10 mm diameter and 2 mm thickness were prepared for each cement. The thermal expansion measurements were performed by strain gauge technique. Four samples of each cement were prepared using silicone rings of 5 mm diameter and 2 mm thickness. The data were analyzed statistically using the Student t test. The setting time obtained for the MTA-Angelus and CER cements was 15 (SD 1) min and 7 (SD 1) min, respectively. The linear coefficient of thermal expansion was 8.86 (SD 0.28) mu strain/degrees C for MTA-Angelus and 11.76 (SD 1.20) mu strain/degrees C for CER. The statistical analysis showed significant difference (P < .05) in the setting time and linear coefficient of thermal expansion between the 2 cements. The CER cement has a coefficient of expansion similar to dentin, which could contribute to a decrease of microleakage degree.